2019
DOI: 10.1038/s41416-019-0626-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced glutamine uptake influences composition of immune cell infiltrates in breast cancer

Abstract: BACKGROUND: Cancer cells must alter their metabolism to support proliferation. Immune evasion also plays a role in supporting tumour progression. This study aimed to find whether enhanced glutamine uptake in breast cancer (BC) can derive the existence of specific immune cell subtypes, including the subsequent impact on patient outcome. METHODS: SLC1A5, SLC7A5, SLC3A2 and immune cell markers CD3, CD8, FOXP3, CD20 and CD68, in addition to PD1 and PDL1, were assessed by using immunohistochemistry on TMAs construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 59 publications
4
38
0
Order By: Relevance
“…Lack of glutamine and glucose in the TME may shift ratios of T cell subsets by supporting the development of regulatory T cells (Treg) rather than effector T cells such as T helper 1 (Th1) cells and Th17 cells ( 1 , 27 , 28 ). For example, the overexpression of SLC1A5, SLC3A2, and SLC7A5 in breast cancer is significantly associated with the existence of Foxp3+ Tregs and poor patient survival ( 29 ). Treg cells and other infiltrating regulatory cells, such as highly anabolic tolerogenic dendritic cells, also compete for the nutrients and contribute to the nutrient-limited TME.…”
Section: The Tumor Microenvironment: a Battlefield With Limited Nutrientsmentioning
confidence: 99%
“…Lack of glutamine and glucose in the TME may shift ratios of T cell subsets by supporting the development of regulatory T cells (Treg) rather than effector T cells such as T helper 1 (Th1) cells and Th17 cells ( 1 , 27 , 28 ). For example, the overexpression of SLC1A5, SLC3A2, and SLC7A5 in breast cancer is significantly associated with the existence of Foxp3+ Tregs and poor patient survival ( 29 ). Treg cells and other infiltrating regulatory cells, such as highly anabolic tolerogenic dendritic cells, also compete for the nutrients and contribute to the nutrient-limited TME.…”
Section: The Tumor Microenvironment: a Battlefield With Limited Nutrientsmentioning
confidence: 99%
“…Cancer metabolism affects the whole TME and drives the insurgence of drug resistance, jeopardizing immunotherapy efficiency [ 113 ]. El Ansari and colleagues [ 114 ] developed an siRNA-based strategy targeting SLC7A5, which mediates the efflux of glutamine and the influx of leucine and is upregulated in breast cancer [ 115 ]. Interestingly, siRNA-mediated SLC7A5 knockdown resulted in a decrease in PD-L1 expression level within the tumor.…”
Section: Sirna Therapeutics Targeting the Tmementioning
confidence: 99%
“…Previous studies have shown that CD4 + T cells and tumor-associated macrophages (TAMs) play a central role in pro-tumor immunity; their interactions with tumor cells can directly promote tumor growth, progression, invasion, and metastasis. Conversely, CD8 + T cells are responsible for antitumor responses, and increased CD8 + T cell infiltration usually indicates a better prognosis in LIHC (Yan et al, 2018;Ansari et al, 2020;Li et al, 2020). In summary, these data indicate that PDZD11 is not only a prognostic biomarker, but may also reflect the immune status of LIHC patients.…”
Section: Discussionmentioning
confidence: 76%